The Effect of Adding Moringa Leaf Extract to TCG Medium on the Post-Thawing Sperm Quality of Donggala Bull - Yohan Rusiyantono; Mohamad Ilyas Mumu; Mobius Tanari; Indriani; Moh Asril Adjis (Jurnal Ilmiah AgriSains, 2026)
This study aimed to evaluate the effect of Moringa (Moringa oleifera) leaf extract (MLE) diluted in Tris-Citric Acid-Glucose (TCG) extender on post-thawing quality of Donggala cattle sperm in. Semen samples were collected from Donggala bulls using an artificial vagina. The semen sample were then pooled and diluted with TCG supplemented with MLE. Three different concentrations of MLE (0 mg/mL, 0.5 mg/mL, 1.0 mg/mL, and 1.5 mg/mL) were tested to evaluate the post thawing motility and viability of Donggala cattle sperm. A standard cryopreservation procedure was used to freeze the semen and storagedin liquid nitrogen container. Sperm motility were valuated under light microscopy while sperm viability was assesed using eosin-nigrosin staining procedures.  The results showed that post-thaw sperm motility and viability were significantly maintained compare to control group following the addition of MLE at 1.0 mg/mL (p < 0.05). The conclusion that moringa leaf extract at a concentration of 1.0 mg/mL in TCG medium provides optimal cryoprotection, improving the post-thaw quality of Donggala bull sperm. This natural additive may serve as a promising supplement in semen extenders to enhance artificial insemination outcomes and genetic conservation efforts.